Traces of Our Interregnum: Selections from an Early Pandemic Archive. Issue 2 (3rd July 2022) - Allums, Coleman A.
Abstract : Interregnum is that moment of crisis in society wherein forces of dislocation and disruption cause, or at least open space for, the potential collapse or reorganization of hegemonic order, the space of the not-yet and, as such, epistemically opaque. It is this image which perhaps best captures those early and unsettling days of the pandemic: moments and spaces which I now attempt to represent herein through selected meditations on everyday life. These meditations—or traces as I see them now, were initially written in the spring and summer of 2020. I resurrect them in a world meaningfully distinct from that of those first weeks, a world all too similar still.